Implementasi Manajemen Risiko Keperawatan untuk Meningkatkan Keselamatan Pasien di Puskesmas Kabupaten Aceh Utara - Harkensia, Linur Steffi; Setia Budi; Atikah, Nurul; Maulani, Ulfa (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Patient safety is closely related to the quality of health services provided. Patient safety and security is still the main focus of attention in health services because the risks associated with providing these services cannot be completely eliminated and the impact they cause is very large. The aim of the research is to analyze the implementation of nursing risk management to improve patient safety at the Sawang Community Health Center. The independent variable in this research is nursing risk management, the dependent variable in this research is patient safety. This research uses a quantitative type of research. The research design used is a cross sectional approach. The population in this study was 41 nurses at the Sawang community health center. Meanwhile, the total sample used was 41 nurses. Based on the results of the chi square test, results were obtained with p value=0.000 that ρ value<α means there is a relationship between nursing risk management and patient safety. It is hoped that the innovations that have been created together, such as monitoring instruments for implementing risk management and online flyers, can be carried out on an ongoing basis to improve patient safety.